2007
DOI: 10.1101/gad.1539307
|View full text |Cite
|
Sign up to set email alerts
|

Infrequently transcribed long genes depend on the Set2/Rpd3S pathway for accurate transcription

Abstract: The presence of Set2-mediated methylation of H3K36 (K36me) correlates with transcription frequency throughout the yeast genome. K36me targets the Rpd3S complex to deacetylate transcribed regions and suppress cryptic transcription initiation at certain genes. Here, using a genome-wide approach, we report that the Set2-Rpd3S pathway is generally required for controlling acetylation at coding regions. When using acetylation as a functional readout for this pathway, we discovered that longer genes and, surprisingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
245
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 188 publications
(270 citation statements)
references
References 40 publications
(62 reference statements)
25
245
0
Order By: Relevance
“…Furthermore, previous study in Saccharomyces cerevisiae has shown that ϳ25% of the total genome displayed a significant increase of H4ac following deletion of Set-2. The genes with longer sequence and less often transcribed display a stronger dependence on the Set2-Rpd3S pathway (44). These studies indicate that SET-2 may have a global effect on gene regulation.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Furthermore, previous study in Saccharomyces cerevisiae has shown that ϳ25% of the total genome displayed a significant increase of H4ac following deletion of Set-2. The genes with longer sequence and less often transcribed display a stronger dependence on the Set2-Rpd3S pathway (44). These studies indicate that SET-2 may have a global effect on gene regulation.…”
Section: Discussionmentioning
confidence: 74%
“…In Saccharomyces cerevisiae, Set2-mediated H3K36me3 maintains a hypoacetylation state of transcribed genes (28,29,31,32), especially for genes with long sequence and transcribed less often (44). Based on these studies, we wondered whether SET-2 affects the histone acetylation level at frq locus.…”
Section: Deletion Of Set-2 Results In Hyperacetylation Of Frq Open Rementioning
confidence: 99%
“…We have previously shown that deletion of SET2 or RCO1 results in a genome-wide increase of acetylated H4 (AcH4) at coding regions, which peaks toward the 3Ј end of the ORFs (17). This change is likely due to the loss of Lys-36 methylation because the profile of distribution changes resembles FIGURE 5.…”
Section: Rpd3s Recognizes Nucleosomes Methylated At Differentmentioning
confidence: 99%
“…Eaf3 and Rco1 are subunits of the Rpd3S histone deacetylase complex; they target this complex to the Lys-36 methylated coding regions of transcribed genes. The recruitment of Rpd3S is responsible for maintaining a hypoacetylated state at coding regions throughout the entire genome, which in turn suppresses cryptic transcription initiation from within the body of the genes (13)(14)(15)(16)(17). This pathway also represses meiotic recombination at certain hot spots in budding yeast (18).…”
mentioning
confidence: 99%
“…Subsequent studies revealed that H3K36me2 is the preferred substrate for Rpd3(S) binding (12)(13)(14) and that a primary function for H3K36 methylation is to recruit the repressive activity of Rpd3(S) to genes to "reset" or reestablish chromatin structure between multiple rounds of transcription (15)(16)(17). Such resetting, or at least maintaining a more compact chromatin structure within gene bodies, also protects genes from spurious transcription from improper initiation sites (cryptic transcription) (15)(16)(17)(18). To date, no separate function has been reported for H3K36me3.…”
Section: Methylation Of Lysine 36 On Histone H3 (H3k36) Is Catalyzed mentioning
confidence: 99%